Temporal Resolvability Analysis of Macroscopic Morphological Development in Neonatal Cerebral Magnetic Resonance Images - Momeni, Maryam; Moghaddam, Hamid Abrishami; Grebe, Reinhard; Gondry-Jouet, Catherine; Wallois, Fabrice (Neuropediatrics, 2014)
Objectives Reliable gradation of neonatal brain development is important for clinical investigation of neurological disorders. A prerequisite for such quantification of development is knowledge about temporal resolvability.Methods We hypothesized 2-week interval as the temporal resolvability of age-related templates to study macroscopic morphological brain development in the early weeks after birth. Therefore, we constructed two templates for the gestational age (GA) ranges of 39 to 40 and 41 to 42 weeks using T1-weighted magnetic resonance (MR) images. Then, we compared the spatial variation of anatomical landmarks and the average and the maximal length of spatial deformation in 30 subjects normalized to the two templates along x, y, and z directions.Results Multivariate analysis of variance (MANOVA) revealed significant difference between spatial variations of the above macroscopic features in the two age ranges. Furthermore, quantitative analysis of feature scattering yielded the same result even in features for which the null hypothesis was not rejected by MANOVA. Moreover, the same procedure was reiterated on two sets of subjects with the closer age range of 1 week (40 and 41 week's GA) and no significant difference could be detected.Conclusions The results strengthen the hypothesis that 2-week is the temporal resolvability of age-related templates for macroscopic morphological studies of the developing brain in the early weeks after birth.
Keywords: neonate; brain development; template; temporal resolvability; spatial deformation; magnetic resonance imaging